Pharmacokinetics and Metabolite Profiling of Trepibutone in Rats Using Ultra-High Performance Liquid Chromatography Combined With Hybrid Quadrupole-Orbitrap and Triple Quadrupole Mass Spectrometers - Sun, Zhi; Yang, Jie; Liu, Liwei; Xu, Yanyan; Zhou, Lin; Jia, Qingquan; Shi, Yingying; Du, Xiangyu; Kang, Jian; Zuo, Lihua (Frontiers in Pharmacology, 2019)
Trepibutone was widely used for cholelithiasis, cholecystitis, biliary tract dyskinesia, cholecystectomy syndrome and chronic pancreatitis in clinic. However, few investigations on trepibutone have been conducted. In this study, an accurate, sensitive and selective analytical method was developed and successfully applied to assess the pharmacokinetic behavior of trepibutone in rats. Trepibutone and carbamazepine (internal standard, IS) were quantified using multiple reaction monitoring (MRM) mode with the transitions of m/z 311.09→265.08 and m/z 237.06→194.08, respectively. The linearity, precision, accuracy, extraction recovery, matrix effect and stability of the established method were all excellent within acceptable range. Totally, thirty metabolites were identified in plasma and urine in total by Q-Exactive high resolution mass spectrometry, and several common metabolic pathways were observed such as dealkylation, oxidation, reduction, glucuronidation and so on. The research provides more information of trepibutone in pharmacodynamics and toxicology and will assist the usage in clinic.